PEDAGOGICAL COMPETENCE DEVELOPMENT OF UNIVERSITY TEACHERS WITH NON-EDUCATION BACKGROUND: THE CASE OF A LARGE UNIVERSITY OF EDUCATION IN INDONESIA - Novianti, Nita; Nurlaelawati, Iyen (International Journal of Education, 2019)
Pedagogical competence of university teachers or lecturers has lately gained much attention from researchers; however, no research has specifically examined the pedagogical competence of lecturers with a non-education background. Herein, drawing upon Olsson et al. (2010) pedagogical competence development and under the Indonesian legislation of lecturer pedagogical competence, we investigated the efforts made by lecturers with a non-education background in a large Indonesian university of education to develop their pedagogical competence. As many as 40 lecturers took part in our preliminary survey of lecturer pedagogical development, and 20 of them joined our interviews and focus group discussions. Based on the results of the survey and focus group discussions, we gained a description of the efforts made by the lecturers in developing their pedagogical competence, their perceptions of the extent to which their university has facilitated their pedagogical development, and the perceived challenges. Recommendations are drawn based on the results of the research to create a model of pedagogical competence development that is suitable for the lecturers and lecturers with a non-education background in general.